Effectiveness of the OZiva® plant-based HerBalance supplement in the management of polycystic ovary syndrome: a real-world evidence study - Upadhyay, Ratna; Gadani, Mihir C.; Tendulkar, Nikita S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovary syndrome (PCOS) is a complex heterogeneous endocrine disorder that is characterized by polycystic ovaries, chronic anovulation, and hyperandrogenism. We evaluated the efficacy and safety of OZiva® Plant Based HerBalance for PCOS (HBPCOS) supplement therapy on females suffering from symptoms and signs of PCOS. Methods: This study employed a retrospective, questionnaire-based design to gather real-world evidence. A total of 153 female participants between the age range of 20-50 years diagnosed with PCOS or related symptoms were enrolled in this study. Primary data was collected using an electronic diary, capturing demographic characteristics and pre- treatment and post-treatment statuses of PCOS clinical signs and symptoms. Results: In this, Female participants, with an average age of 28.70 ± 5.34 years. years and a history of PCOS for an average duration of 3 months, were recruited. Of the female participants, >87% of those with menstrual cramps, >92% with menstrual bleeding issues, 80% with acne, 64% with excess facial hair, 74% with weight management issues, 61% with difficulty conceiving, and >68% with irregular menses experienced complete or partial resolution of their symptoms after three months of consuming OZiva® HBPCOS. There was a statistically significant improvement in symptoms across the participants. Conclusion: This study shows that PCOS-related infertility, obesity/difficulty managing weight, menstrual issues, and dermatological symptoms/signs have been significantly reduced after consuming OZiva® HBPCOS product for 3 months.